Evidence for a Cystic Fibrosis Enteropathy. - Marlou P M Adriaanse; Linda J T M van der Sande; Anita M van den Neucker; Paul P C A Menheere; Edward Dompeling; Wim A Buurman; Anita C E Vreugdenhil (PLoS ONE, 2015)
Previous studies have suggested the existence of enteropathy in cystic fibrosis (CF), which may contribute to intestinal function impairment, a poor nutritional status and decline in lung function. This study evaluated enterocyte damage and intestinal inflammation in CF and studied its associations with nutritional status, CF-related morbidities such as impaired lung function and diabetes, and medication use.Sixty-eight CF patients and 107 controls were studied. Levels of serum intestinal-fatty acid binding protein (I-FABP), a specific marker for enterocyte damage, were retrospectively determined. The faecal intestinal inflammation marker calprotectin was prospectively studied. Nutritional status, lung function (FEV1), exocrine pancreatic insufficiency (EPI), CF-related diabetes (CFRD) and use of proton pump inhibitors (PPI) were obtained from the medical charts.Serum I-FABP levels were elevated in CF patients as compared with controls (p<0.001), and correlated negatively with FEV1 predicted value in children (r-.734, p<0.05). Faecal calprotectin level was elevated in 93% of CF patients, and correlated negatively with FEV1 predicted value in adults (r-.484, p<0.05). No correlation was found between calprotectin levels in faeces and sputum. Faecal calprotectin level was significantly associated with the presence of CFRD, EPI, and PPI use.This study demonstrated enterocyte damage and intestinal inflammation in CF patients, and provides evidence for an inverse correlation between enteropathy and lung function. The presented associations of enteropathy with important CF-related morbidities further emphasize the clinical relevance.